Nutritional diagnosis in adult patients with Chronic Intestinal Failure: Glim criteria or Subjective Global Assessment - M. Ortega; A. Crivelli; P. Klin; G. Gondolesi; H. Solar (Intestinal Failure)
Background: Patients with Chronic Intestinal Failure (CIF) present increased risk for malnourishment. Nutritional assessment is commonly done through the Subjective Global Assessment (SGA). The Global Leadership Initiative on Malnutrition (GLIM) developed phenotypic and etiologic criteria for assessing and grading malnutrition. The aims of this study were to determine malnutrition in CIF patients comparing the GLIM criteria and SGA and determine the severity of malnutrition according to the GLIM phenotypic criteria. Material and methods: From June 2019 through December 2021 a retrospective analysis was conducted. All patients had a diagnosis of CIF. Malnutrition was evaluated using the SGA and the GLIM criteria, while the degree of malnutrition according to the phenotypic criteria. Observational, bivariate, multiple logistic regression and ROC analyses were performed. Results: Seventy patients with CIF were included. The mean age was 47.8 years, 51.4 % being female. The SGA showed 27 % of the patients were moderately malnourished and 33 % were severely malnourished. According to the GLIM criteria, 86 % of the patients presented at least one phenotypic criterion of malnutrition. Regarding the etiologic criteria all the patients had reduced food intake and/or impaired absorption or food assimilation. When grading malnutrition status 53 % presented moderate malnutrition and 33 %, severe malnutrition. The ROC analyses showed an area under the curve (AUC) of 0.92 for the SGA and 0.86 for the GLIM criteria (p = 0.98). Conclusion: In this study, a higher percentage of patients with malnutrition was diagnosed according to the GLIM criteria, although, when comparing ROC analyses, no statistical difference was found.